Pemanfaatan Blog Pribadi Di Instagram Sebagai Media Komunikasi Parenting (Studi Deskriptif Kualitatif Akun Instagram @annisast) - Gan Gan Giantika (Universitas Bina Sarana Informatika, 2019)
Abstract - Instagram has become a popular social media, because everyone is also competing to populate themselves with their Instagram account, one of the personal blog accounts in the instragam account that @annisast uses its account as a communication medium that provides information and education to users of Instagram account other. The purpose of this research is to find out the utilization and process of utilizing personal blogs on Instagram as a parenting communication media. Research uses a qualitative research approach, a type of qualitative descriptive study research. The result of the research is the @annisast instagram account in his personal blogging, there is the use of instagram as a parenting communication media, one of which is in the image titled from upload both in terms of many followers who appreciate it, can be seen from the thanks for the tips and the discussion in the comment column, upload the uploaded photo namely everyday photos with children and images that match the theme of the tips discussed, the title of the photo in accordance with the parenting discussion, namely